Bernarda Francisca das Chagas: um estudo de caso sobre a acusação de adultério julgada no Tribunal da Relação de Pernambuco (1820 -1825). - Bezerra, Tânia Cristina Costa (2021)
This case study presents an analysis of the Appeal for Judgment on a complaint of adultery tried in the Province of Pernambuco during the validity of the Philippine Ordinances. This set of laws, regarding the crime of adultery, provided in Book V, Title XXV, the death penalty for women convicted of that practice. Just as in Title XXXVIII it granted the husband authorization to kill his wife if he caught her in adultery. Our primary source, the process, was analyzed together with historiographical texts on the subject in order to reach an understanding of the social context of the time, an understanding of the use of laws as an instrument to legitimize diverse interests and customs standardized by religious rules. The research aimed to identify the forms of access to justice and the possible motivations that led the plaintiff to seek legal action in this case. The result of this analysis was the elaboration of a Digital Booklet with educational purposes aimed at undergraduates of history and law. We believe that this study will contribute to the understanding of the formation of laws under the influence of religious and philosophical principles and women's space in this context.